Measures against pine weevil Hylobius abietis also reduce damage by Hylastes cunicularius and Hylastes brunneus - Wallertz, Kristina; Hjelm, Karin; Eriksson, Stefan (TAYLOR AND FRANCIS AS, 2024)
Hylastes species are known to cause damage to conifers in plantations in northern Sweden, and in recent years an increase in seedling damage has been observed in southern Sweden. However, there are few studies on Hylastes spp and the damage it can cause, so there is a lack of knowledge regarding pest management. In order to investigate an eventual interaction between damage by Hylastes spp and the more well-known Hylobius abietis (L) we registered damage by these species. Unprotected spruce seedlings were compared with seedlings protected from Hylobius abietis by a mechanical coating or with an insecticide. The effect of mechanical site preparation (MSP) was studied, with half of the seedlings being planted in unprepared soil and the other half after MSP. Both seedling protection and MSP significantly reduced the level of damage caused by Hylastes spp. MSP reduced the proportion of affected and killed seedlings and reduced the level of damage at the root collar. Protecting the seedlings reduced the level of damage, and no difference was found between seedlings treated with an insecticide and those provided with a coating. Similar responses were observed with both containerized and plug plus seedlings. In conclusion, measures against Hylobius abietis seem to also prevent damage by Hylastes spp.